EMI-EMC Qualification of the NASA SWOT Mission Using High Fidelity Modeling - Nacer E. Chahat; Edward Gonzales; Emmanuel Decrossas; Amy Stevens; Matthew Keyawa; Pablo S. Narvaez (IEEE Journal of Microwaves)
Surface Water and Ocean Topography (SWOT) is a complex satellite with multiple high-power transmitters and highly sensitive receivers. A pivotal feature is the Ka-band interferometer, operating at 2000 Watts, which significantly amplifies the satellite's qualification challenges. Additionally, the utilization of an X-band low-gain antenna for high data rate communication necessitates meticulous characterization and early-stage mitigation strategies to prevent interference with nearby instruments. Throughout the spacecraft's development lifecycle, meticulous attention was devoted to high-fidelity RF coupling to validate the compatibility between all instruments and preempt potential late-stage setbacks. This paper provides a comprehensive overview of the rigorous modeling and testing methodologies employed to ascertain the satellite's self-compatibility, ensuring mission success and reliability.